Analisis Kesesuaian Hukum Ekonomi Syariah Terhadap Usaha Jasa Titip (Studi Kasus Pembelian Tiket Konser Para K-Pop Fans) - Ardana, Niken Ayu (Peneliti.net, 2024)
The delivery service business is one of the various types of businesses that are currently developing, especially in Indonesia. In this business, many business owners provide offers for the delivery service itself, one of the offers provided by the delivery service business actors, which is about purchasing concert tickets for Idols or K-Pop Artists who are now in demand by young people. This delivery service businees is in great by K-Pop Idols or Artists will hold concerts or performance. The purpose of this writing is to find out the practices and conditions provided by the delivery service business provider have conformity with sharia economic law. This research is a qualitative research with content analysis data collection technique namely by analyzing the points of the conditions given from jastip providers to jastip users.